Implementasi Program Kampus Merdeka Dalam Kegiatan MSIB7 Studi Independen Pada Yayasan Decoding Indonesia - Sembiring, Lismardiana; Duma Lasmaria Siagian; Monang Tarigan; Dede Prabowo Wiguna; Jenheri Rejeki Tarigan (ULINA: Jurnal Pengabdian kepada Masyarakat, 2025)
MBKM (Merdeka Belajar – Kampus Merdeka) is a program provided by the Ministry of Education, Research, and Technology (Kemenristek) to improve the quality of education in Indonesia. One of the most popular MBKM programs is the MSIB Program (Certified Independent Study and Internship Program). Internship based on MBKM (Merdeka Belajar Kampus Merdeka) is an internship/work practice program that can be taken by students who have completed at least semester 5 of their studies. This program is a form of university collaboration with industry to provide independent learning. The purpose of MBKM is to hone hard skills and soft skills to suit the needs of the times and be ready to welcome the world of work. MSIB (Certified Independent Study and Internship), this program allows students to do internships at companies or take learning to increase their knowledge in the world of work. Independent Study Program is a non-degree learning program organized by organizations or industries that provide knowledge and skills with a high level of relevance in the world of work and business in the form of short courses, bootcamps, massive open online courses (MOOCs), and others, which are continued with collaborative activities with fellow participants or partner organization personnel in a project or case study. The following are the characteristics of Independent Study certified by Kampus Merdeka. For MSIB7 as a partner of MBKM Yayasan Decoding Indonesia, the MBKM team is entrusted as a means of certified learning assisted by DPP (Program Supervisor) whose participants are all lecturers throughout Indonesia who have been declared to have passed as DPP by Kampus Merdeka.